The complete chloroplast genome sequence of the Dioscorea persimilis Prain et Burkill (Dioscoreaceae) - Cao, Tianxu (Mitochondrial DNA B Resour, 2020)
Dioscorea persimilis belongs to Dioscorea genus, which is considered as one of the most popular food and traditional folk medicine in China. The complete chloroplast genome of D. persimilis was determined in this study. The total genome size was 153,219 bp in length, containing a pair of inverted repeats (IRs) of 25,477 bp, which were separated by large single copy (LSC) and small single copy (SSC) of 83,448 bp and 18,817 bp, respectively. The GC content is 37.01%. A total of 129 genes were predicted including 84 protein-coding genes, eight rRNA genes and 37 tRNA genes. Phylogenetic tree analysis of 24 species in the genus Dioscorea indicated that D. persimilis was closer to Chinese yam, but has remote phylogenetic relationship with Guinea yam.